Performance Comparison Between Direct and External Modulation Using RZ and NRZ Coding - Hadj Ali, Bakir (ELEKTRIKA- Journal of Electrical Engineering, 2020)
Such as in any optical communication system, the light modulation is considered a main key to determine the performance (or the maximum) of the data rate that can be transmitted and over what the long distance can be applied. So, a choice of the modulation type in any optical link is more important and should base on measuring of the BER and the Q factor parameters. In that issue, we propose a comparative study as contribution between the principle or the schemes of the direct modulation (DM) and the external modulation (EM) respectively, which the chirp frequency modeling is described for the two modulations. However, the main issues addressed also in the simulation analysis when the amount of the chirp (in GHz) introduced for the two modulations applied is discussed, and also the Q factor introduced using different power values and, in different data rate for the two modulations studied is presented where we can determine from these results of the Q factor the effect of the power and the limit of applying the direct modulation and the external modulation in terms of the maximum of the data rate that can be transmitted. Moreover, we provide a numerical results of the Q factor and the BER for the two modulations (DM and EM) using RZ and NRZ format codes at different distance transmission, and in different data rate through these results we can conclude in which code (RZ and NRZ) the DM and the EM performed better.